2020
DOI: 10.1155/2020/6412916
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Exercise in Nonalcoholic Fatty Liver Disease: ERS-Linked Molecular Pathways

Abstract: Nonalcoholic fatty liver disease (NAFLD) is globally prevalent and characterized by abnormal lipid accumulation in the liver, frequently accompanied by insulin resistance (IR), enhanced hepatic inflammation, and apoptosis. Recent studies showed that endoplasmic reticulum stress (ERS) at the subcellular level underlies these featured pathologies in the development of NAFLD. As an effective treatment, exercise significantly reduces hepatic lipid accumulation and thus alleviates NAFLD. Confusingly, these benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 151 publications
0
12
0
Order By: Relevance
“…To simulate the E167K condition and explore the influence of TM6SF2 on lipid accumulation, we generated TM6SF2-knockdown cells in both the L02 and HepG2 cell lines (Figure 3A ), which were incubated with PA (150 μmol/L) or BSA (fatty acid free) for 24 h. We found that TM6SF2-knockdown cells demonstrated higher levels of intracellular TG (Figure 3B ) and more severe lipid accumulation (Figure 3C ). Lipid overload induces endoplasmic reticulum stress (ERS) and causes cell death[ 28 , 29 ]. The cell viability assay results proved that TM6SF2 knockdown markedly exacerbated PA-induced cell death (Figure 3D ), which reflected the increase in lipid content in the TM6SF2-knockdown group.…”
Section: Resultsmentioning
confidence: 99%
“…To simulate the E167K condition and explore the influence of TM6SF2 on lipid accumulation, we generated TM6SF2-knockdown cells in both the L02 and HepG2 cell lines (Figure 3A ), which were incubated with PA (150 μmol/L) or BSA (fatty acid free) for 24 h. We found that TM6SF2-knockdown cells demonstrated higher levels of intracellular TG (Figure 3B ) and more severe lipid accumulation (Figure 3C ). Lipid overload induces endoplasmic reticulum stress (ERS) and causes cell death[ 28 , 29 ]. The cell viability assay results proved that TM6SF2 knockdown markedly exacerbated PA-induced cell death (Figure 3D ), which reflected the increase in lipid content in the TM6SF2-knockdown group.…”
Section: Resultsmentioning
confidence: 99%
“…Presently, there is no clear conclusion regarding the impact of different exercise methods, exercise intensity, and exercise duration on ER stress intensity and stress duration in different tissues. In an 8-week swimming training study on HFD-fed rats, aerobic exercise is found to significantly reduce ER stress in rat liver tissue and testicular fat [ 47 ]. Three months of aerobic exercise is found to reduce GRP-78, IRE1, and p-eIF2 α mRNA and protein levels in subcutaneous fat tissue and blood mononuclear cells of obese adults [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the current therapeutic outcomes for dealing with NAFLD-related metabolic pathologies are unsatisfactory [ 32 ]. In line with this, exercise has been proposed as an effective treatment strategy for NAFLD through various mechanisms, such as the upregulation of antioxidant enzymes and anti-inflammatory mediators and through the regulation of the endoplasmic reticulum stress-associated pathways [ 33 , 34 ]. In light of these studies, we identified the HFD-induced NAFLD-linked protein expression profile in sedentary and exercise intervention mouse models through a high-throughput quantification of proteins.…”
Section: Discussionmentioning
confidence: 99%